Improving the prediction of environmental fate of engineered nanomaterials by fractal modelling. (February 2017) - Avilov, S.; Lamon, L.; Hristozov, D.; Marcomini, A.
Abstract: A critical analysis of the available engineered nanomaterials (ENMs) environmental fate modelling approaches indicates that existing tools do not satisfactorily account for the complexities of nanoscale phenomena. Fractal modelling (FM) can complement existing kinetic fate models by including more accurate interpretations of shape and structure, density and collision efficiency parameters to better describe homo- and heteroaggregation. Pathways to including hierarchical symmetry concepts and a route to establishing a structural classification of nanomaterials based on FM are proposed. Highlights: Fractal modeling can improve the accuracy of input parameters used in existing multimedia mass balance models. Symmetry is relevant for modelling self-assembled systems at the nanoscale. Deterministic fractals can be used to create a classification of shape properties of nanomaterials.